Extracolonic findings with the PillCam Colon: is panendoscopy with capsule endoscopy closer? - Romero-Vázquez, Javier; Caunedo-Álvarez, Ángel; Belda-Cuesta, Alba; Jiménez-García, Victoria Alejandra; Pellicer-Bautista, Francisco; Herrerías-Gutiérrez, Juan Manuel (Endoscopy International Open, 2016)
Background and study aims: Colon capsules display images from the moment they are ingested, making the study of other extracolonic areas possible. The aim of this study was to analyze the significance of these extracolonic findings.Patients and methods: In this single-center, prospective study, 165 patients underwent colon capsule endoscopy (CCE) between September 2009 and October 2012 to rule out colonic pathology. Images were recorded, without interruptions, from the moment the capsule was ingested until its battery ran out. The study was deemed complete when the capsule had traveled from the esophagus to excretion or until the hemorrhoidal plexus was observed. Results: CCE was used for colorectal cancer (CRC) screening (81.2 %), to investigate for chronic diarrhea (9.7 %) and chronic iron deficiency anemia (6.1 %), and for patients with incomplete colonoscopy (3.0 %). The capsule returned findings in the esophagus in 52.1 % of patients, in the stomach in 45.5 % of patients, and in the small bowel in 70.7 % of patients, with the findings being considered relevant in 4.9 %, 9.7 %, and 22.6 % of patients, respectively. The whole extent of the digestive tract was fully recorded in 86.1 % of patients and the Z line could be fully observed in 57.6 % of patients. There were no adverse events.Conclusions: CCE allows the recording of images from almost the whole extent of the digestive tract in most patients, enabling relevant pathologies to be identified in extracolonic areas, particularly the small bowel. Technical and procedural improvements are still necessary in order to achieve better observation of the stomach and esophagus.